(untitled) (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article presents the outcomes of a community service initiative in Sumbergedang Village, Pandaan District, Pasuruan Regency, aimed at instilling a culture of environmental care and nurturing the creative economy. The study implemented various work programs, including the development of Information Technology-Based Micro, Small, and Medium Enterprises (MSMEs). Employing a mixed-methods approach, the research demonstrated significant improvements in people’s motivation to create a cleaner and more comfortable environment while bolstering the growth of the community’s creative economy. The implications of this study highlight the potential for similar interventions to drive positive environmental and economic changes in rural communities worldwide. Highlights: • Development of Information Technology-Based MSMEs: The study focuses on leveraging modern technologies to support the growth of Micro, Small, and Medium Enterprises (MSMEs) in the community. • Environmental Stewardship: The initiative aims to instill a sense of responsibility and care for the environment among the residents of Sumbergedang Village. • Nurturing Creative Entrepreneurship: The project fosters an environment that encourages innovation and creativity, leading to the development of the community’s creative economy. Keywords: Environment, Creative Economy, MSME, Information Technology, Community Service